2010
DOI: 10.1212/wnl.0b013e3181f4d821
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and psychosocial features in childhood and juvenile MS

Abstract: Our findings confirm the importance of systematic assessment of cognitive and psychosocial issues in children and teens with MS. The progressive nature of the cognitive difficulties emphasizes the need for developing effective treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
217
4
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 30 publications
11
217
4
4
Order By: Relevance
“…6,20,35,37,46 Investigations into the relationship between fatigue and neurocognitive functioning suggested that fatigue is unrelated to overall neurocognitive functioning. 6,[40][41][42] However, there was some evidence to suggest that fatigued caMS have impaired performance on some individual cognitive tasks, particularly motor-based tasks such as the Trail Making Test A and B, and on tasks requiring prolonged and complex mental activity, such as problem solving, complex attention and processing speed, and language comprehension tasks. 6,33 At present, the evidence does not substantially support a relationship between fatigue and any specific domain of cognitive functioning.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…6,20,35,37,46 Investigations into the relationship between fatigue and neurocognitive functioning suggested that fatigue is unrelated to overall neurocognitive functioning. 6,[40][41][42] However, there was some evidence to suggest that fatigued caMS have impaired performance on some individual cognitive tasks, particularly motor-based tasks such as the Trail Making Test A and B, and on tasks requiring prolonged and complex mental activity, such as problem solving, complex attention and processing speed, and language comprehension tasks. 6,33 At present, the evidence does not substantially support a relationship between fatigue and any specific domain of cognitive functioning.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…[3][4][5][6] Additionally, in POMS subjects, there is accumulating evidence of involvement of linguistic faculties 1,6 and lower intellectual efficiency in terms of intelligence quotient (IQ), particularly in those with younger age at MS onset. 7 An early MS disease onset can have a negative influence in school achievements and overall quality of life, [8][9][10][11] but it is unclear if it could lead to an increased risk for CI in later life. 3 Some studies suggest a negative impact of relapses, disease duration and physical disability in the cognitive performance of patients with POMS, 8,9,12 but these issues remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…3 Some studies suggest a negative impact of relapses, disease duration and physical disability in the cognitive performance of patients with POMS, 8,9,12 but these issues remain controversial. 10,11 There is little information about the long-term cognitive outcome in patients with POMS. Longitudinal studies published to date have relatively short followup periods (1-5 years), and suggest cognitive worsening, with variable rates of decline, although there are patients who may exhibit stable or improved cognitive function over time.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of MS in a developing brain and early cognitive dysfunction are major concerns that can be evaluated only in children and cannot be extrapolated from studies in adults. 6,7,21,22 Cognitive function should be addressed in any therapeutic trial and requires the development of a core battery of neuropsychological tests applicable to international cross-sectional and longitudinal studies in pediatric MS. Challenges include differences in developmental trajectories and patterns of cognitive dysfunction in relation to patient age.…”
Section: Resultsmentioning
confidence: 99%
“…Current research is limited by variable tools used by different research groups, preventing pooling of data across studies, and limited availability of validated assessment tools with satisfactory norms. 6,[21][22][23] Requirements for cognitive batteries to be used in pediatric MS clinical trials are listed in table 3.…”
Section: Resultsmentioning
confidence: 99%